Management of childhood obesity and overweight in paediatric out-patient setting. (29th September 2015) - Puttha, R; Lee, C; Crabbe, S; Menakaya, C; Horton, N; Bone, M
Abstract : Aim: The aim of this study is to review how efficiently hospital paediatricians are identifying, assessing and managing children with overweight or obesity in out-patient setting when they were referred for obesity or any other health problems. Method: The authors conducted this prospectively in two hospitals, one, a district general and the other a children's hospital. The clinical notes and letters on all patients attending paediatric out-patients, over a selected period of time, were reviewed in detail. The authors specifically looked at the identification, any kind of assessment or management of the weight. The authors used the body mass index (BMI) of 98th centile or above for obesity and BMI above 91st centile for overweight as recommended by National Institute of Clinical Excellence guideline 1. Results: Of the 105 children audited in a district general hospital (DGH) 31% were found to be obese (21%) and overweight (10%). In the children's hospital (CH) 24% were obese and 5% overweight, out of the 42 children we audited. None of the overweight children in both hospitals were identified as overweight and did not have any type of tailored intervention or assessment. 47% of the obese patients in the DGH and 62% of them in CH were identified and had some sort of assessment. Comorbidities were assessed in 75% of patients who were recognised to be obese in CH and only in 18% in DGH. Conclusion: Overweight children are not identified appropriately, be it in a children's or district general hospital. There is higher recognition and assessment of obese children in CH than district general though more than 40% are still not identified. Training and the importance of recognition, assessment and management of obesity and overweight has to be improved, even by Paediatricians working in hospitals, considering the fact that it is a modifiable risk factor and has a potential risk of major chronic health problems like hypertension and diabetes.